2019
DOI: 10.3390/v11030213
|View full text |Cite
|
Sign up to set email alerts
|

A Lactic Acid Bacteria (LAB)-Based Vaccine Candidate for Human Norovirus

Abstract: Human noroviruses (HuNoVs) are responsible for more than 95% of the non-bacterial acute gastroenteritis epidemics in the world. The CDC estimates that every year 21 million individuals suffer from HuNoV-induced gastroenteritis in the United States. Currently, there is no FDA-approved vaccine for HuNoVs. Development of an effective vaccine has been hampered by the lack of an efficient cell culture system for HuNoVs and a suitable small animal model for pathogenesis study. In this study, we developed lactic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Subsequently, they were separated from sow feeding and provided with artificial milk powder as their source of nutrition. The results reveal that after three rounds of immunization, significant weight gain was observed in the piglets along with elevated levels of serum IgG antibodies [ 49 ]. Furthermore, when exposed to a full dose of diarrhea, these immunized piglets demonstrated protection against it [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, they were separated from sow feeding and provided with artificial milk powder as their source of nutrition. The results reveal that after three rounds of immunization, significant weight gain was observed in the piglets along with elevated levels of serum IgG antibodies [ 49 ]. Furthermore, when exposed to a full dose of diarrhea, these immunized piglets demonstrated protection against it [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, L. lactis was not found in the differential flora, indicating that L. lactis could not colonize the gastrointestinal tract for a long time. Relevant studies have shown that L. lactis can only survive for 4 h in the human gastrointestinal tract (GIT) [ 53 ], and when dead in the gastrointestinal tract, it cannot spread in the environment, which makes it safer as a genetically modified organism (GMO) [ 45 , 49 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite considerable effort, the propagation of noroviruses by conventional cell culture techniques is not yet routine; however, efforts to overcome these obstacles are making progress (462)(463)(464)(465)(466). Human noroviruses do not infect other normal animal hosts; however, several studies with human norovirus conducted in gnotobiotic (germ-free) piglets suggest that vaccine candidates and probiotics can at least partially suppress clinical symptoms, viral replication, and shedding in these animals (467)(468)(469)(470).…”
Section: Norovirus Epidemiology Pathogenesis and Antigenic Diversity ...mentioning
confidence: 99%
“…In the last decade, scientific interest has focused on the application of this group of food-grade bacteria as effective vehicles for mucosal delivery and for the delivery of recombinant prophylactic and therapeutic proteins, neutralizing antibodies, and the variable domain of heavy-chain-only antibodies from camelids-known as VHH antibodies or nanobodies-into the human gut, to prevent and treat inflammatory bowel diseases (IBDs), autoimmune disorders, infectious and non-infectious gastrointestinal diseases, and infections by pathogenic microorganisms from mucosal surfaces [18,[21][22][23][24][25][26]. As lactic acid bacteria (LAB) is a cell factory and delivery vehicle for the delivery of therapeutic proteins, an LAB strain (Lactococcus lactis) was used as a vector to deliver HuNoV (human noroviruses) antigen and it demonstrated that this LAB-based HuNoV vaccine induced protective immunity in gnotobiotic piglets [27].…”
Section: Introductionmentioning
confidence: 99%